Pregnancy Exercise Shorten the Duration of the Second Stage of Labor - Saputra, Mahendra Eko; Wigati, Kristanti Wanito; Prasetyo, Budi (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Background : There are several factors that contribute to duration of labor, which are power, passage, and passenger. Pregnancy exercise is one of many interventions that can be done in favor of increasing power during labor.Aim : The purpose of this study was to investigate the correlation between pregnancy exercise and second stage of labor duration.Material and Methods: This was an analytic observational study using cross sectional design conducted in Al-Irsyad Hospital in Surabaya. The total sample was 48 pregnant women who followed pregnancy exercise program and did not follow pregnancy exercise program that met sample criteria. Medical records data on duration of second stage of labor and pregnancy exercise program data were collected then analyzed by mann-whitney test.Results: The mean second stage of labor in pregnancy exercise group was 25.88±13.21 minutes, while in non-pregnancy group was 11.46±4.77 minutes. The analysis using mann-whitney test showed a significant correlation between pregnancy exercise and second stage of labor (p=0.000).Conclusion: There was a significant correlation between pregnancy exercise and second stage of labor. Pregnancy exercise shorten the duration of second stage of labor.